ANALISIS KELEMBAGAAN PENGELOLAAN EKOSISTEM MANGROVE DI DESA KELAPA PATI - Trisla Warningsih; Rasoel Hamidy; Wardatul Hidayah (Jurnal Sosioteknologi, 2020)
The degradation of mangrove ecosystems in Bengkalis Regency is caused either one by mangrove ecosystems management that are still not optimal. The research of institutional analysis of mangrove ecosystem management in Kelapa Pati Village was conducted in November 2019 in the mangrove ecosystem of Kelapa Pati Village, Bengkalis District, Bengkalis Regency. The assessing of institutional  role about mangrove ecosystems management in Kelapa Pati Village was carried out based on in-depth interviews with informants in the form of selected stakeholders. Institutional analysis of mangrove ecosystems shows that the mangrove ecosystem institutions in Kelapa Pati Village are grouped into: Key players (Managers, Village Heads, Regents, Dinas Lingkungan Hidup dan Kehutanan Provinsi, Dinas Lingkungan Hidup Kabupaten), context setters (DPRD), crowds (Dinas PU , BAPPEDA, Dinas Perikanan, NGO, and University); and subjects (community and community leaders).